Protein determinations of iodine in pregnancy - Subauste P., Carlos (2015)
In 65 normal pregnant protein iodine numbers are determined via the technique of chloric acid. In the first trimester of pregnancy is an average value of 8.82 ug%; in the second quarter 10 ug% in the third quarter and 11.99 ug%; These elevations Iodine protein in normal pregnancy as due to increased estrogen, in turn, cause an increase in transport capacity of the thyroid hormone binding proteins, not increasing the free thyroxine are interpreted, which explains the absence of clinical symptoms of hyperthyroidism.